2016
DOI: 10.1093/infdis/jiw527
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with Chronic Hepatitis C and cirrhosis compared to the general population – a Danish cohort study

Abstract: MRs were high among patients with CHC with or without cirrhosis compared with the general population. Curing CHC was associated with a reduction in MR among cirrhotic patients, but the MR remained higher than the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 33 publications
2
18
1
2
Order By: Relevance
“…These trends were dominated by a rise in HCV‐associated cirrhosis and HCC, with a much smaller contribution from NAFLD and ALD . Another recent study from Europe demonstrated a reduction in mortality rate associated with achieving sustained virologic response among patients with HCV‐related cirrhosis . In our study, a steep decline in the HCV‐related mortality rate was observed during the DAA era from 3.68 per 100,000 persons in 2014 to 3.2 per 100,000 persons in 2016, with a rate of 6.5% decline per year.…”
Section: Discussionsupporting
confidence: 50%
“…These trends were dominated by a rise in HCV‐associated cirrhosis and HCC, with a much smaller contribution from NAFLD and ALD . Another recent study from Europe demonstrated a reduction in mortality rate associated with achieving sustained virologic response among patients with HCV‐related cirrhosis . In our study, a steep decline in the HCV‐related mortality rate was observed during the DAA era from 3.68 per 100,000 persons in 2014 to 3.2 per 100,000 persons in 2016, with a rate of 6.5% decline per year.…”
Section: Discussionsupporting
confidence: 50%
“…The benefit of treatment for those with mild inflammation or fibrosis is less certain. Since the risk of complications increases dramatically once cirrhosis develops, it is of particular importance to detect patients with early cirrhosis …”
Section: Introductionmentioning
confidence: 99%
“…With regard to our study, one possible explanation could be that our study was a real life cohort study with expectedly less than perfect surveillance assuming that surveillance provides a survival benefit . Our current study exclusively included CHC patients with cirrhosis and the cohort showed a high prevalence of alcohol overuse, IDU, decompensation and psychiatric disease—all of which are associated with poor survival and negatively associated with surveillance . With regard to HCC treatment, we only had reliable data on LTX, and we found that nine patients (7.8%) received LTX after HCC.…”
Section: Discussionmentioning
confidence: 95%
“…Differences in the application of LTX are likely to reflect national and regional traditions and availability of organs as well as eligibility of patients. We attribute the poor survival in this study to the advanced HCC stage and the high overall mortality of the cohort …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation